2020
DOI: 10.1016/j.pmedr.2020.101211
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity is associated with multiple chronic conditions and physical health status among older US adults

Abstract: In the past two decades, food insecurity has increased by 45% among older adults but its relationship to health outcomes has not been extensively studied. The objective of this study was to examine the associations between food insecurity, multiple chronic conditions, and self-reported health status among a nationally representative sample of older U.S. adults. Data came from the National Poll on Healthy Aging, a national cross-sectional survey conducted in December 2019 among 2,048 individuals aged 50-80 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 22 publications
3
58
0
2
Order By: Relevance
“…We also assess sleep quality because insufficient sleep has been associated with a range of negative health and social outcomes, including lower labor productivity ( Hafner, Stepanek, Taylor, Troxel, & van Stolk, 2017 ). Similarly, food security, or access to sufficient, nutritious food, is a critical health outcome, and is also associated with multiple health and social conditions ( Gundersen and Ziliak, 2015 , Leung et al, 2020 ). Finally, we assess both cognitive and affective dimensions of perceived risk (residents’ estimates of catching COVID-19 and worry about getting sick) because these are associated with people’s capacity to respond to risk and manage their health and wellbeing during infectious disease outbreaks ( Brooks, Dunn, Amlôt, Rubin, & Greenberg, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…We also assess sleep quality because insufficient sleep has been associated with a range of negative health and social outcomes, including lower labor productivity ( Hafner, Stepanek, Taylor, Troxel, & van Stolk, 2017 ). Similarly, food security, or access to sufficient, nutritious food, is a critical health outcome, and is also associated with multiple health and social conditions ( Gundersen and Ziliak, 2015 , Leung et al, 2020 ). Finally, we assess both cognitive and affective dimensions of perceived risk (residents’ estimates of catching COVID-19 and worry about getting sick) because these are associated with people’s capacity to respond to risk and manage their health and wellbeing during infectious disease outbreaks ( Brooks, Dunn, Amlôt, Rubin, & Greenberg, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…An emerging body of literature has documented associations between food insecurity and chronic disease in individuals at older ages, including diabetes, heart disease, hypertension, kidney disease, obesity, and pulmonary disease. 3 , 4 , 6 , 10 , 11 , 12 , 13 , 14 , 15 Studies have reported that food-insecure older adults in the US and Canada were subject to higher mortality risk and shorter life spans than their food-secure peers. 16 , 17 , 18 , 19 , 20 Despite considerable evidence of its health consequences, little is known about the mechanisms by which food insecurity causes adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Another nationally representative, cross-sectional study using data from NHANES also revealed that age-standardized rates of food insecurity were greater in participants with hypertension (14.1% vs. 11.1%, P = 0.0003) [ 22 ]. We found one study, based on data from the National Poll on Healthy Aging, that did not find significantly greater hypertension prevalence when comparing food-insecure with food-secure older adults (aged 50–80 years) (40.3% hypertension among food-secure adults vs. 46.7% among food-insecure adults, P = 0.10) [ 23 ]. However, this study did not report adjusted results for this comparison, so the lack of difference may be explained by confounding, or possibly by overall high prevalence of hypertension in this age group.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, recent literature suggests an association between CKD and food insecurity. A cross-sectional study looking at a nationally representative sample of older US adults found that chronic kidney disease was more common in those with food insecurity, compared with those who were not experiencing food insecurity (5.6% vs. 2.0%, P = .005) [ 23 ]. An important longitudinal study from Banerjee et al examined 2,320 adults with CKD in the NHANES III study [ 42 •].…”
Section: Resultsmentioning
confidence: 99%